BENTUK KATA RAGAM BAHASA GAUL DI KALANGAN PENGGUNA MEDIA SOSIAL INSTAGRAM - Widya Dara Anindya; Vita Novian Rondang (Prasasti: Journal of Linguistics)
Social media was a proof of the rapid development in information technology. It was in line with the appearance of slang words formed by its users. Most of social media users were teenagers. The rapid of vacabulary creation of slang language was a proof of linguistics creativity formed by social media’s users mostly teenagers. This research aimed to identify words form of slang language found in instagram feeds and comments column. The data was slang words collected by using observation methods with screenshot and note taking techniques. Data was taken from instagram feeds and comments of @dagelan and @memecomic.id. The result showed that words forms of slang language classified into some forms, namely (1) acronym, (2) abreviation, (3) contraction, (4) klipping, (5) walikan form, (6) borrowing from foreign language, (7) association, (8) monophonization, (9) infiltration of vocal letters, (10) words formed by improving from original words, and (11) new words formed of the creativity of instagram users.